Study advocates for poverty preference admissions at selective institutions. Issue 3 (May 2016) - Sutton, Halley
Abstract : Low‐income students, even those who perform very highly academically in high school, account for only 3 percent of enrolled students at the 200 most selective institutions nationwide. A new report released by the Jack Kent Cooke Foundation suggests that based on these findings, top colleges should create admissions preferences for low‐income students.